Climate‐relevant behavioral spillover and the potential contribution of social practice theory. (7th July 2017) - Nash, Nick; Whitmarsh, Lorraine; Capstick, Stuart; Hargreaves, Tom; Poortinga, Wouter; Thomas, Gregory; Sautkina, Elena; Xenias, Dimitrios
Abstract : Urgent and radical transition to lower‐carbon forms of society is imperative to limit current and future climate change impacts. Behavioral spillover theory offers a way to catalyze broad lifestyle change from one behavior to another in ways that generate greater impacts than piecemeal interventions. Despite growing policy and research attention, the evidence for behavioral spillover and the processes driving the phenomenon are unclear. The literature is split between studies that provide evidence for positive spillover effects (where an intervention targeting an environmentally conscious behavior leads to an increase in another functionally related behavior) and negative spillover effects (where an intervention targeting an environmentally conscious behavior leads to a decrease in another functionally related behavior). In summarizing findings, particular attention is given to the implications for climate‐relevant behaviors. While few examples of climate‐relevant behavioral spillover exist, studies do report positive and negative spillovers to other actions, as well as spillovers from behavior to support for climate change policy. There is also some evidence that easier behaviors can lead to more committed actions. The potential contribution of social practice theory to understanding spillover is discussed, identifying three novel pathways to behavioral spillover: via carriers of practices, materiality, and through relationships between practices within wider systems of practice. In considering future research directions, the relatively neglected role of social norms is discussed as a means to generate the momentum required for substantial lifestyle change and as a way of circumventing obstructive and intransigent climate change beliefs. WIREs Clim Change 2017, 8:e481. doi: 10.1002/wcc.481 This article is categorized under: Perceptions, Behavior, and Communication of Climate Change > Behavior Change and Responses Abstract : One route through which social practices may evolve, overlaid with spillover processes identified by Thøgersen. 140 (Reprinted with permission from Ref 140. Copyright 2012 Sage Publications)